Quantifying the ecosystem services values of electricity generation in the US Chihuahuan Desert: A life cycle perspective - Jordaan, Sarah M.; Lee, Junghun; McClung, Maureen R.; Moran, Matthew D. (Journal of industrial ecology, 2021)
Despite increasing attention, the quantification of ecosystem services values in life cycle assessment (LCA) remains nascent relative to other impact categories. In this analysis, we develop and implement a novel approach for quantifying both land requirements and ecosystem services values based on The Economics of Ecosystems and Biodiversity framework. Our case study focuses on energy infrastructure in the US portion of the Chihuahuan Desert, a location that has high resource potential for multiple types of energy. The analysis focuses on the land requirements of three types of power plants from a life cycle perspective: natural gas, solar, and wind. The mean land‐use intensity for natural gas, solar, and wind electricity is estimated to be 0.27, 0.68, and 0.064 meters squared per Megawatt‐hour (m2/MWh), respectively. When considering cumulative land use of the upstream natural gas supply chain, solar breaks even with gas within 10 years. Mean ecosystem services costs are $0.54, $1.39, and $0.12 USD/MWh for electricity generated from natural gas, solar, and wind, respectively. Ecosystem services costs for developments in this region are low relative to levelized costs of electricity (<5%) but are subject to low values compared to other types of ecosystems. Results will vary with regionalized ecosystem services values and different products. Although the results of this study are specific to electricity generation in the Chihuahuan Desert with 2016 as the baseline year, our approach is applicable across regions, scales, and product systems within LCA. This article met the requirements for a gold‐silver JIE data openness badge described at http://jie.click/badges.